Current situation of job burnout and its influencing factors among workers in a chemical fiber factory in Xinxiang City, Henan Province - Jia MA; Hui WU; Sanqiao YAO; Shanfa YU (环境与职业医学, 2023)
BackgroundJob burnout is prevalent among the occupational population, which may lead to individual physical and mental discomfort and affect the quality of life and productivity of suffered workers. Most current chemical fiber factory workers are engaged in hazardous tasks with high frequency and high repetition, which are highly associated with anxiety and depressive symptoms, and subsequently lead to job burnout. ObjectiveTo understand the current situation and influencing factors of job burnout in workers of a chemical fiber factory in Xinxiang City of Henan Province, and to provide empirical evidence for preventing and reducing the occurrence of job burnout in target workers. MethodsIn 2022, the workers of a chemical fiber factory in Xinxiang City were selected by cluster random sampling. The Chinese versions of the Burnout Scale, Generalized Anxiety Disorder-7, and Patient Health Questionnaire-9 were used to conduct a survey. SPSS 25.0 software was used for rank sum test, correlation analysis, and logistic regression analysis. ResultsA total of 1463 valid questionnaires were collected, with an effective recovery rate of 90.0%. The positive rate of mild and moderate job burnout in the chemical fiber factory employees was 39.4%, and the positive rate of serious job burnout was 14.3%. There were statistical differences in the positive rates of job burnout among the workers by gender, age, education level, position, work shift system, anxiety symptom severity, and depressive symptom severity (P<0.05). The results of Spearman correlation analysis showed that the score of anxiety symptoms was positively correlated with the total score of job burnout, as well as the dimensional scores of exhaustion and cynicism, and negatively correlated with the dimensional score of professional efficacy (r=0.671, 0.764, 0.673, −0.097; P<0.01). The score of depressive symptoms was also positively correlated with the total score of job burnout, as well as the dimensional scores of exhaustion and cynicism, and negatively correlated with the dimensional score of professional efficacy (r=0.688, 0.791, 0.723, −0.087; P<0.01). The results of logistic regression analysis showed that men had a higher risk of serious job burnout than women (OR=1.698, 95%CI: 1.163-2.479); workers aged ≤ 40 years old had a higher probability of serious job burnout than those aged 51 to 60 years old (OR=2.587, 95%CI: 1.310-5.109); non-assembly line production workers and assembly line production workers were more prone to serious job burnout than administrative management and logistics personnel (OR=6.511, 9.707, 95%CI: 1.539-27.548, 2.260-41.700); compared with other shift systems (three shifts and night shifts), the probability of serious job burnout was lower (OR=0.375, 95%CI: 0.254-0.553) in regular day shift workers; compared with frequent overtime work, those reporting no overtime work and occasional overtime work showed a lower risk of serious job burnout, with OR (95%CI) values of 0.114 (0.068-0.192) and 0.331 (0.194-0.564), respectively. ConclusionThe positive rate of job burnout among the employees of the chemical fiber factory is high, and the anxiety symptoms and depressive symptoms are positively correlated with job burnout. Adjustment of work should be strengthened at multiple levels to improve anxiety symptoms and depressive symptoms of employees, and reduce the occurrence of job burnout.